Pursuing Expanded Criteria Donors as Candidates for Kidney Donation after Circulatory Death. (June 2014) - DeLario, Ginger T.; Quetschenbach, Jim; Croezen, Donna; Niedfeldt, Danielle; Landon, Julie
Of the 119 310 people on the national transplant waiting list, 97 280 people are waiting for kidneys. There simply are not enough organs to meet the demand. Recognizing that 64% of the people waiting for kidney transplants are at least 50 years old, this organ procurement organization embarked on a study to evaluate the potential of increasing the number of viable kidneys available for transplant by pursuing expanded criteria donors as donation after circulatory death (ECD/DCD) candidates. Pursuing ECD/DCD donors resulted in 24 additional donors (50–67 years old), 48 kidneys recovered, 30 kidneys transplanted into 26 recipients (44–74 years old), 7 kidneys placed for research, and 11 kidneys discarded, yielding an overall 62% transplant rate, 15% research rate, and 23% discard rate. The overall discard rate including all donors in all classifications during the study period was 13.1% (122 discards from 928 kidneys) compared with 12.6% (111 discards from 880 kidneys) when the study set was excluded. Although ECD/DCD donors still had the highest discard rates of all the groups, the 0.5% increase in the overall discard rate due to pursuing ECD/DCD kidneys was considered insignificant when compared with the benefit of the 30 additional kidneys transplanted. Including potential ECD/DCD patients in the donor pool increases the number of viable kidneys available for transplant without significantly increasing the overall kidney discard rates.